Course of instruction in dancing and aesthetic development of the body - Segadlo, L. F. (Newark, N.J., 1889)
This is a translation by Segadlo of an article, by an unknown author, found in the Universal Gazette, published in Vienna, Austria. It is a strong defense of dance and exercise, a subject that was often discussed during the late nineteenth century. The manual concludes with three sets of quadrilles as taught by the author, "Princeton University Lancers," "Saratoga Lancers," and the plain quadrille.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance; Quadrille (Dance) -- Handbooks, manuals, etc; Dance Instruction and Physical Culture